The Ethiopian staple food crop enset (Ensete ventricosum) assessed for the first time for resistance against the root-lesion nematode Pratylenchus goodeyi - Kidane, S.; Meressa, B.H.; Haukeland, Solveig; Hvoslef-Eide, A.K.; Coyne, D. (Brill, 2021)
Pratylenchus goodeyi appears to be the most prevalent nematode pest of enset in Ethiopia, where it can occur in extremely high densities. However, the damage to yield or how different enset cultivars react to the nematode has yet to be determined. The current study therefore sought to establish a first assessment of these reactions by enset to P. goodeyi infection. Determining pest-resistant cultivars is an important task in developing management strategies. Our study evaluated nine enset cultivars to establish host response and identify potential sources of resistance. In addition, the pathogenicity of P. goodeyi was assessed on three enset cultivars. After 9 months’ growth, significant differences in final population densities (Pf) and reproduction factor (RF) were observed amongst the nine cultivars, with ‘Gefetanuwa’ the most susceptible (Pf = 25 799 and RF = 12.9), and similarly in a repeat experiment for 4.5 months (Pf = 126 534 and RF = 63.3). ‘Maziya’ and ‘Heila’ were the most resistant in the first experiment (Pf < 455 and RF < 0.2) as well as in the repeat, together with ‘Kellisa’ (Pf < 5255 and RF < 2.6). In the pathogenicity experiment four inoculum densities significantly affected the Pf and RF but not among the three cultivars ‘Maziya’, ‘Arkiya’ and ‘Heila’. This is the first known study to assess genotype reaction to P. goodeyi, which shows that there are significant differences in the reactions of different cultivars and that resistance appears to be present in enset.